Development of Dynamometer Based on Strain Gauge with Sensor Rod Type Four Square Stalk to Measuring the Drive Power of Rotary Friction Welding Machine - Yohanes Yohanes; Muhammad Rahdiyat Alqolbi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2020)
Friction welding is a type of solid state welding where the welding process is carried out in the solid phase. In the welding process there are several components that work, namely the electric motor as the main mover. This study aims to developmant a dynamometer to measure the mechanical power of a rotary friction welding machine. Dynamometer development includes the design, manufacture, calibration and testing of dynamometers. Dynamometer design that will be placed on the holder that serves as a stretch bar. Dimension of the strain dynamometer is 35 mm × 4 mm × 70 mm and serves to determine the motor torque value with the help of a 120 Ohm strain gauge sensor and to measure power it needs an additional speed sensor or optocoupler sensor to measure the motor angular speed. In need of making a microcontroller or an electrical device. Finally, the dynamometer testing process on a rotary friction welding machine. When the welding process takes place, the greater the pneumatic pressure exerted during welding, the more measurable the power is. The largest power value measured in the forging phase is 2408.50 Watts and the smallest power measured by the dynamometer is 2050.24 Watts at the initial rotation.